(untitled) (Altre Modernità, 2010)
The article offers a reading of the staging of The Magic Flute by visual artist William Kentridge, focusing on his introduction of the rhino in the visual landscape of the opera as symbol for the silenced subject of violence. Operatic tradition has always been concerned with the staging of death, in particular with the death of its female protagonists, and recent scholarship has highlighted the complicity of the genre with the ideology of Western patriarchy and colonial violence. In this light, Kentridge’s appropriation stages Mozart’s opera as both voice of colonial Europe and place of resistance for the postcolonial artist. Kentridge moves the setting of the opera to colonial Africa, and the Flute becomes haunted with the massacre of the Herero people in South West Africa by the German army led by general von Trotha (1904-1907). The African white rhino, a species under the threat of extinction, works in this work as proxy for the missing corpses of the Herero people; in its being subject to humiliation and ruthless murder, it recalls Judith Butler’s recent attempt at a different categorization of human life as both a continuous exposure to violence and what can be mourned after death. With its silence among the powerful sounds of Mozart’s opera, the body of the dead, dancing rhino stands at the centre of Kentridge’s work, which becomes a ceremony of mourning where the Western canon can be made to "resonate differently" (Trinh T. Minh-ha).